PAKISTAN-UNITED STATES RELATIONS DURING OPERATION ENDURING FREEDOM (2001-2014): CARROT AND STICK APPROACH AT WORK - Muhammad Ali; Riaz Nadeem; Shahzad Nadeem (International Journal of Contemporary Issues in Social Sciences, 2024)
In close temporal proximity of September 11, 2001 attacks, Pakistan-US relations were at the unprecedented lowest ebb. Consequential upshots of said attacks not only redesigned global political ambiance infusing a renewed focus on combating terrorism, particularly through "Operation Enduring Freedom" in Afghanistan, but also necessitated convalescence of sanctions-stricken Pakistan-US relations. Ostensibly, Pakistan’s geo-strategically vital location in immediacy of landlocked Afghanistan prompted the US to recuperate its relations with Pakistan by any means necessary. Henceforth, the US put coercive diplomacy at work and aligned Pakistan with itself before launching Operation Enduring Freedom in Afghanistan and thenceforward incessantly practiced “carrot and stick” approach to ensure Pakistan’s unwavering engagement and methodical support of US led Operation Enduring Freedom in Afghanistan. This paper attempts to examine "carrot and stick" approach which eventually hybridized the relationship as well as investigates the multifariousness of divergent interests of Pakistan and the US in Afghanistan throughout the Operation Enduring Freedom (2001-2014) through employing realist framework. It seeks to comprehend major areas of mutual cooperation e.g. incentives, concessions, financial or military aid, as well as principal irritants and frictions including trust deficit, divergent interests and insensitivity of US towards reservation of Pakistan etc.